Working memory and second language acquisition: effects on vocabulary, grammar, reading, and writing - Riki Nasrullah, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This research explores the role of working memory in L2 acquisition, attempting to provide c insight into how individual variations in working memory capacity lead to variability in language learning performance. A descriptive correlational research design was employed to examine the natural variations in working memory and their relationship with English proficiency among high school students in Surabaya, Indonesia. Participants were divided into high and low-working memory groups. Their performance was measured based on four aspects of language: vocabulary, grammar, reading comprehension, and writing. Results showed that working memory positively correlates with language proficiency in reading comprehension, vocabulary, and grammar. On the other hand, this trend is weaker in writing. Using linear regression analysis, working memory predicted performance in three aspects: vocabulary, grammar, and reading comprehension. These findings indicate the significance of individualized teaching methodologies concerning individual cognitive potential. The study concludes by calling for adaptive language teaching techniques that exploit working memory for efficient L2 learning while at the same time calling for further research into instructional approaches and other cognitive factors affecting language acquisition.